2017
DOI: 10.1111/ipd.12314
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the conventional and biological treatment approaches for the management of caries in the primary dentition

Abstract: Background In the last few years, conventional restorations including complete removal of carious tissue (CT) with or without pulp therapy for the treatment of carious lesions (CL) in primary teeth have been challenged and a more biological approach has been suggested. This approach involves the use of less invasive techniques which alter the environment of the CL isolating it from the cariogenic biofilm and substrate. Two of these treatment approaches that are becoming increasingly widely accepted and used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 16 publications
4
40
1
1
Order By: Relevance
“…This can be explained by the fact that the two treatment approaches demonstrated similar successful outcomes as demonstrated in several specialist‐based RCTs and cohort studies. A recent study reported 95.8% and 95.3% of the primary teeth that were restored using the conventional and biological approaches, respectively, remained asymptomatic over 6‐year follow‐up. This high success rate would contribute to the improvement of the overall health status and quality of life of the participants reported in this study.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This can be explained by the fact that the two treatment approaches demonstrated similar successful outcomes as demonstrated in several specialist‐based RCTs and cohort studies. A recent study reported 95.8% and 95.3% of the primary teeth that were restored using the conventional and biological approaches, respectively, remained asymptomatic over 6‐year follow‐up. This high success rate would contribute to the improvement of the overall health status and quality of life of the participants reported in this study.…”
Section: Discussionsupporting
confidence: 72%
“…From the child and carer perspectives, the conventional and biological approaches were equally associated with significant improvement in the child and family's oral health‐related quality of life in this study. This can be explained by the fact that the two treatment approaches demonstrated similar successful outcomes as demonstrated in several specialist‐based RCTs and cohort studies. A recent study reported 95.8% and 95.3% of the primary teeth that were restored using the conventional and biological approaches, respectively, remained asymptomatic over 6‐year follow‐up.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations